Partijraad Zutphen 29 september 1984. . Vlnr.: Van den Berg, Faber, Reuvenkamp,?, staand De Jong - Clerkx, Ebbo, (1984)
Partijraad Zutphen 29 september 1984. Vlnr.: Van den Berg, Faber, Reuvenkamp,?, staand De Jong.